New insights into force depression in skeletal muscle - Joumaa, V.; MacIntosh, B. R.; Herzog, W. (The Journal of Experimental Biology, 2012)
Force depression observed following active shortening is not well understood. Previous research suggested that force depression might be associated with a stress-induced inhibition of cross-bridges in the newly formed overlap zone following shortening. Our aim was to investigate this theory in skinned fibres and determine whether there was an inhibition of the attachment of cross-bridges or a decrease in the force produced per cross-bridge. The stress-induced inhibition of cross-bridge theory gives testable predictions, including: (1) skinned fibres should show proportional force and stiffness depression, (2) force after shortening should not be lower than force before shortening, (3) stiffness following shortening should not be lower than stiffness before shortening and (4) force depression should decrease when the stress during shortening is decreased. In agreement with these predictions, force and stiffness depression were approximately proportional, and force depression decreased with decreasing stress during shortening. However, in contrast to the predictions of the stress-induced inhibition of cross-bridge theory, force after shortening from sarcomere lengths of 2.8 and 3.0 micro m to a sarcomere length of 2.4 micro m was smaller than force before shortening, and this was not accompanied by a corresponding decrease in stiffness. We conclude that the stress-induced inhibition of cross-bridge theory, as proposed previously, cannot be the only mechanism for force depression, but that there is an additional, stress-induced inhibition of cross-bridges in the old overlap zone. Furthermore, both mechanisms, inhibition of cross-bridge attachment and reduction of force produced per cross-bridge, contribute to force depression. Inhibition and/or reduction of force depend(s) on the amount of stress imposed on actin during the shortening phase.